Makna Denotatif dan Konotatif Pantun Lagu Tanjung Katung - Nayla Nayla Azzahra; Rithaony Hutajulu; Hubari Gulo (Mahesa Research Center, 2026)
This study examines the meaning of pantun texts in the song Tanjung Katung performed by Orkes Melayu Lebah Begantong. It aims to identify and analyze denotative and connotative meanings and to understand their function in performance contexts. The study employs a qualitative method with a descriptive-analytical approach using observation, interviews, and documentation. Data analysis is based on Ferdinand de Saussure’s semiotic theory. The findings reveal that denotatively, pantun depict daily life, nature, and social situations, while connotatively, they express symbolic meanings such as gratitude, respect, humor, and social interaction. The improvisational delivery makes meanings dynamic and context-dependent. Thus, pantun functions not only as aesthetic elements but also as a medium of social communication, reflecting Malay cultural values.